2017
DOI: 10.1186/s12902-017-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-reactive protein, interleukin 6, tumor necrosis factor alpha and glycemic load associated with type 2 diabetes mellitus in rural Thais: a cross-sectional study

Abstract: BackgroundThe elevated levels of inflammatory markers, including C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), and interleukin 6 (IL6) are supposed to be associated with type 2 diabetes mellitus (T2DM). Frequent high glycemic load (GL) consumption, central obesity, and a lack of physical activity are considered to be T2DM risk factors. This study aimed to determine the difference of these inflammatory markers as well as GL in individuals with versus those without T2DM in rural Thais.MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 29 publications
9
53
3
1
Order By: Relevance
“…TNF -α, as a kind of non glycosylated protein, can induce the body to produce IR by promoting the decomposition of fat granules, increasing FFA, reducing the activity of insulin receptor tyrosine kinase and interfering with normal insulin signal transduction. Therefore, this study suggests that a high level of in ammatory response in KKAy mice are related to the occurrence of T2DM, which is consistent with the research results of chanchira phosat et al [ 22] on T2DM population.…”
Section: Discussionsupporting
confidence: 92%
“…TNF -α, as a kind of non glycosylated protein, can induce the body to produce IR by promoting the decomposition of fat granules, increasing FFA, reducing the activity of insulin receptor tyrosine kinase and interfering with normal insulin signal transduction. Therefore, this study suggests that a high level of in ammatory response in KKAy mice are related to the occurrence of T2DM, which is consistent with the research results of chanchira phosat et al [ 22] on T2DM population.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, besides the cognitive dysfunction produced by DM, hippocampal levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β were significantly increased (p<0.05) in non-treated diabetic rats compared with negative control group. Consistent with our work, studies found that chronic hyperglycemia promotes the generation of different intracellular inflammatory pathways, including inflammatory mediators such as TNF-α, IL-6, and C-reactive protein (CRP ) [39,40]. Similarly, a study by S. Takeda et al in a transgenic mouse model of AD and diabetes reported that Aβ-induced synaptic dysfunction was positively correlated with elevated levels of cytokines and tumor necrosis factor (TNF-α) [41].Also, Shamim et al,.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated CRP and IL6 levels were associated with increased risk of developing T2DM. There was a trend towards increased risk of T2DM with elevated TNF-α levels and conclude that, CRP, IL6, and TNF-α associated with T2DM (27). Also other study aimed to investigate the association between elevated tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and high sensitivity-C-reactive protein (hs-CRP) with type 2 diabetes mellitus (T2DM) in abdominal obesity women subjects.…”
Section: Discussionmentioning
confidence: 99%